STUDI PERUBAHAN KUALITAS PASCAPANEN BUAH BELIMBING DENGAN BEBERAPA PENGEMASAN DAN SUHU SIMPAN - Inanpi Hidayati Sumiasih; Linda Octaviani; Dessy Indah Lestari; Endah Ratna Yunita (Agrin, 2016)
Star fruit is a type of fruit that is easily damaged and require a special postharvest handling. Some of thepostharvest handling efforts are by storing at low temperature storage and packaging. Storage at low temperaturecan extend the shelf life and maintain the quality of the star fruit. The purpose of this study is to extend the shelflife and maintain the quality of the star fruit, and to know a good packaging for the star fruit. The star fruit werepicked from the orchid in Tuban, East Java, and the treatment was conducted in the Postharvest Laboratory,University of Trilogy. The research uses randomized complete block design of two factors. The first factor is thetemperature of storage consisting of 18oC temperature and room temperature, the second factor is the packagingconsists of styrofoam + plastic wrap, plastic, foamnet and paper). The data is processed by using the scoringmethod and by collecting from the fixed-trained panelists. Data qualitatively transformed into quantitative databy using the symbol numbers. The research shows that the star fruit which is stored at a temperature of 18oC canextend the shelf life to 14 days after harvest (HSP) with the packaging by using styrofoam + plastic wrap, by usingplastics and foamnet (12 HSP) and by using paper (10 HSP). While the star fruit at room temperature storage,with the packaging by using styrofoam + plastic wrap can extend the shelf life to 8 HSP, and by using foamnet,plastics and paper to 6 HSP.Key words: horticultural commodity, shelf life, the fruit appearance Belimbing merupakan buah yang mudah mengalami kerusakan, maka diperlukan upaya untuk penangananpascapanen yang baik. Salah satu upaya penanganan pascapanen yaitu dengan cara penyimpanan dengan suhurendah dan pengemasan. Penyimpanan dengan suhu rendah dapat memperpanjang masa simpan danmempertahankan kualitas buah belimbing. Tujuan dari penelitian ini adalah untuk memperpanjang masa simpandan mempertahankan kualitas buah belimbing serta mendapatkan cara pengemasan yang baik. Buah belimbingdipetik di kebun Tuban, Jawa Timur dan perlakuan dilaksanakan di Laboratorium Pascapanen, Universitas Trilogi.Penelitian menggunakan rancangan acak kelompok dua faktor. Faktor pertama yaitu suhu simpan terdiri atas (suhu18oC dan suhu ruang), faktor kedua adalah pengemasan terdiri atas (styrofoam + plastik wrap, plastik, foamnetdan kertas). Data skor diolah menggunakan metode skoring. Metode ini dengan cara mengumpulkan dari panelistetap yang terlatih. Data secara kualitatif dirubah menjadi data kuantitatif dengan menggunakan simbol angka.Dari penelitian ini di dapatkan hasil bahwa buah belimbing yang disimpan pada suhu 18oC dapat memperpanjangmasa simpan sampai 14 hari setelah panen (HSP) dengan pengemasan styrofoam + plastik wrap, pada pengemasanplastik dan foamnet (12 HSP) dan pengemasan kertas (10 HSP). Sedangkan buah Belimbing pada penyimpanansuhu ruang, dengan pengemasan styrofoam + plastik wrap dapat memperpanjang masa simpan selama 8 HSP, danpada pengemasan foamnet, plastik dan kertas (6 HSP).Kata kunci: komoditas hortikultura, masa simpan, penampilan buah